Linking gene regulation to cell behaviors in the posterior growth zone of sequentially segmenting arthropods. Issue 3 (May 2017) - Williams, Terri A.; Nagy, Lisa M.
Abstract: Virtually all arthropods all arthropods add their body segments sequentially, one by one in an anterior to posterior progression. That process requires not only segment specification but typically growth and elongation. Here we review the functions of some of the key genes that regulate segmentation: Wnt, caudal, Notch pathway, and pair-rule genes, and discuss what can be inferred about their evolution. We focus on how these regulatory factors are integrated with growth and elongation and discuss the importance and challenges of baseline measures of growth and elongation. We emphasize a perspective that integrates the genetic regulation of segment patterning with the cellular mechanisms of growth and elongation. Highlights: We review segmentation genes in sequentially segmenting arthropods and speculate as to how Wnt, Notch and pair-rule signaling have evolved. We evaluate whether abnormal phenotypes from disrupting Notch signaling are consistent with Notch functioning in a conserved segmentation clock. We describe how cell behaviors are linked to proper function of segmentation genes. We discuss a perspective of growth zone function that integrates segmentation and elongation.